The impact of extreme weather phenomena on public health: An analysis of Indonesia national policies on adaptation/mitigation strategies - Inayah Alfiyah Nur; Paliling Valeria Erika Sari; Maskun Maskun (BIO Web of Conferences)
Global climate change has led to an increase in the frequency of extreme weather phenomena, which have major impacts on public health. In response, Indonesia has developed the National Action Plan for Climate Change Adaptation (RAN-API) to enhance climate resilience. The RAN- API recognizes the health sector as a critical subject for adapting to climate change and establishes three primary goals: (a) Strengthening and updating of information on health risk and vulnerability due to climate change, (b) Development of policies, planning, networking, and cooperation among government agencies at the local, regional and national levels regarding climate change health risk, and (c) Strengthening capacity and early awareness of climate change-related threats to health in the community. However, despite the presence of national policies responding to health impacts due to climate change, the effectiveness of the RAN-API remains limited. This study will analyse the existing national policies regarding mitigation and adaptation programs designed to address climate change impacts of extreme weather phenomena on public health, and giving the contribution to strengthening adaptation and mitigation strategies, including strengthening climate resilience for vulnerable communities.